Service Quality That Affected the Customers for Choosing Flash Express Service in Muang District, Samut Prakan Province - Toomphol, Aeknaree; Sawangkan, Nannaphat; Tochit, Chawanwit; Chaiyakam, Arphutsara (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research aims to study, 1) Satisfaction in using Flash Express service in Mueang District, Samut Prakan Province Classified by demographic factors, and 2) the quality of service affected the decision to use the Flash Express service in Muang District, Samut Prakan Province. The data were collected from the population in the Muang district. Samut Prakan Province who chose to use Flash Express company and by using a questionnaire collected a random sample of 400 users and analyzed it using descriptive statistics, t-test, One-way ANOVA and Multiple Regression Analysis methods. The results showed that; 1) the respondents with different occupations choose the service of Flash Express service differently with the statistically significant at the .05 level, and 2) service quality in the concrete aspect of service reliability, customer confidence, and response to customers affects the decision to use the Flash Express transportation service in Muang District, Samut Prakan Province with statistically significant at the .01 level.